High-Resolution Magnetic Resonance Black Blood Thrombus Imaging and Serum D-Dimer in the Confirmation of Acute Cortical Vein Thrombosis - Song, Si-ying; Dornbos, David; Lan, Duo; Jiao, Bao-lian; Wan, Shu-ling; Guo, Yi-bing; Ding, Yu-chuan; Yang, Qi; Ji, Xun-ming; Meng, Ran (Frontiers in Neurology, 2021)
Cerebral cortical vein thrombosis (CCVT) is often misdiagnosed because of its nonspecific diagnostic symptoms. Here, we analyzed a cohort of patients with CCVT in hopes of improving understandings and treatments of the disease. A total of 23 patients with CCVT (confirmed with high-resolution imaging), who had been diagnosed between 2017 and 2019, were enrolled in this cohort study. Baseline demographics, clinical manifestations, laboratory data, radiological findings, treatment, and outcomes were collected and analyzed. Fourteen females and nine males were enrolled (mean age: 32.7 ± 11.9 years), presenting in the acute (within 7 days, n=9), subacute (8 to 30 days, n=7), and chronic (over one month, n=7) stages. Headaches (65.2%) and seizures (39.1%) were the most common symptoms. Abnormally elevated plasma D-dimers were observed in the majority of acute stage patients (87.5%). The diagnostic accuracy of contrast-enhanced magnetic resonance venography (CE-MRV) and high-resolution magnetic resonance black-blood thrombus imaging (HR-MRBTI) in detecting CCVT were 57.1% and 100.0%, respectively. All patients had good functional outcomes after 6-month of standard anticoagulation (mRS 0-1) treatment. However, four CCVT patients that had cases involving multiple veins showed symptom relief after batroxobin therapy (p = 0.030). HR-MRBTI may be a fast and accurate tool for non-invasive CCVT diagnosis. HR-MRBTI combined with D-dimer can also precisely identify the pathological stage of CCVT. Batroxobin may safely accelerate cortical venous recanalization in combination with anticoagulation. Follow-up studies with larger sample sizes are suggested to evaluate the safety and efficacy of batroxobin for treating CCVT.